Biological Clocks and Rhythms of Anger and Aggression - Hood, Suzanne; Amir, Shimon (Frontiers in Behavioral Neuroscience, 2018)
The body’s internal timekeeping system is an under-recognized but highly influential force in behaviors and emotions including anger and reactive aggression. Predictable cycles or rhythms in behavior are expressed on several different time scales such as circadian (circa diem, or approximately 24-hour rhythms) and infradian (exceeding 24 hours, such as monthly or seasonal cycles). The circadian timekeeping system underlying rhythmic behaviors in mammals is constituted by a network of clocks distributed throughout the brain and body, the activity of which synchronizes to a central pacemaker, or master clock. Our daily experiences with the external environment including social activity strongly influence the clock mechanism operates at the level of our genes, but its exact timing of this network is synchronized by our experiences with the external environment including social activity. In the present review, we examine evidence from a number of species and propose that anger and reactive aggression interact in multiple ways with circadian clocks. Specifically, we argue that i) there are predictable rhythms in the expression of aggression and anger, ii) disruptions of the normal functioning of the body clock circadian system increase the likelihood of aggressive behaviors, and iii) conversely, chronic expression of anger can disrupt normal rhythmic cycles of physiological activities and create conditions for pathologies such as cardiovascular disease to develop. Taken together, these observations suggest that a comprehensive perspective on anger and reactive aggression must incorporate an understanding of the role of the body circadian timing system in these intense affective states.